DEVELOPMENT OF A SMART HOUSE IN THE BIOSYSTEM ENGINEERING COURSE - Matulovic, M. [UNESP]; Neto, M. Mollo [UNESP]; Hiromoto, B. [UNESP]; Eivazian, L. [UNESP]; Ribeiro, M. L. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
Technologies of Industry 4.0 are bringing new opportunities, challenges and solutions to many domains, including agriculture, plant sciences, animal sciences, food sciences and social sciences. In this scenario, not only industrial companies have to learn relevant technologies, but also the academic environment is interested in changes in the educational curriculum to include and reflect on new technologies, concepts and paradigms. The inclusion of 3D printing in school curricula is also positive from another pedagogical perspective, as it can offer opportunities for different learning styles to be practiced. Thus, this research aims to evaluate the work in which students tutored by professors of the Engineering course, develop the planning, construction, instrumentation and elaboration of a supervisory system of a Smart House, in order to base the learning through the construction of a model using 3D printing techniques and instrumentation, thus fixing the concepts of IoT, automation, supervision and control, use of sensors and actuators, PLC programming and the development of supervision and remote control utility applications. The results pointed to the fact that dealing with the theme in an inter and transdisciplinary way proved to be a necessity in Engineering courses at Universities, especially those in which the main objectives lie in the use of technologies in their work and research practices and the experiment. The proposed method provided students with added value in the learning process that ended up transcending the interdisciplinary knowledge inherent in the course itself.
DESENVOLVIMENTO DE UMA SMART HOUSE NO CURSO DE ENGENHARIA DE BIOSSISTEMAS
Keywords: 3D Prototyping; Education 4.0; Sensing; Supervision and Control